HUBUNGAN ANTARA PEMAHAMAN SEJARAH PERGERAKAN NASIONAL INDONESIA DENGAN SIKAP TERHADAP BELA NEGARA - Trisnowaty Tuahunse (Jurnal Kependidikan, 2009)
This study was aimed at finding out how the relation between understanding of Indonesian national movement history and state nurture attitudes of students of State Senior High School of Gorontalo Municipality. The research hypothesis stated that there was a meaningful relation between understandings of Indonesian national movement history and state nurture attitudes. The study used the descriptive quantitative research method. The population was designated as all students of Year II of State Senior High School of Gorontalo Municipality of the precept year of 2006/2007. The sample consisted of 159 students, 15% of the total population of 1060 students. Sampling was done by way of multi-stage random sampling. Data collection was done by tests and questionnaires using the Likert scale. Data analysis was done using the correlation and regression statistical techniques. Results of the correlation analysis showed that, there was a meaningful positive relation between understandings of Indonesian national movement history and state nature attitudes (r. count = 0,424; t. count = 5,87 t. table = 1,96). Results of the regression analysis showed a coefficient measure of understanding of Indonesian national movement history and state nurture attitudes of F. count = 34, 44 F. table (2,157) = 3,91. The statistical figures showed that there was a horizontal relation between students understanding for Indonesian national movement history and their state nurture attitudes. It was concluded that Indonesian national movement history had a contribution in developing nurture state attitudes. Key Words: Indonesian national movement history, state nurture, nationalism.